2017
DOI: 10.1111/bjet.12561
|View full text |Cite
|
Sign up to set email alerts
|

The influence of flow on learning outcomes: An empirical study on the use of clickers

Abstract: Flow is a state of total absorption and concentration in an activity that is desirable for students, as it enhances the learning experience. Due to the importance of flow for learning, this research investigates the influence of three flow preconditions-namely balance of skill and challenge, feedback and goal clarity-on students' flow, operationalized as heightened concentration, sense of control and autotelic experience, while using clickers-a type of polling device. The study also explores the impact of conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…People in a flow state become completely absorbed in their activity and, as they lose self-consciousness, perceive hardly any external stimulus because nothing else seems to matter (Gao et al, 2016;Hsu & Lu, 2004). Literature has shown that flow has a positive effect on learning results and must be considered when digital learning materials are designed (Buil, Catalán, & Martínez, 2017;Lai, Lim, & Wang, 2016).…”
Section: Flow Experiencementioning
confidence: 99%
“…People in a flow state become completely absorbed in their activity and, as they lose self-consciousness, perceive hardly any external stimulus because nothing else seems to matter (Gao et al, 2016;Hsu & Lu, 2004). Literature has shown that flow has a positive effect on learning results and must be considered when digital learning materials are designed (Buil, Catalán, & Martínez, 2017;Lai, Lim, & Wang, 2016).…”
Section: Flow Experiencementioning
confidence: 99%
“…A notion central to the flow theory is that individuals who feel confident that their skills will allow them to face highly demanding situations are more prone to experience flow (Buil, Catalán, & Martínez, 2017). That is to say, flow states occur when e-learning activities require the student to stretch his or her abilities to new levels.…”
Section: Antecedents Of Flowmentioning
confidence: 99%
“…Buil et al (2019) stated that the flow experience is a state where students fully absorb and concentrate on an activity because it enhances the learning experience [48], while research by Erhel and Jamet (2019) showed that flow experience has a positive impact on memory and understanding [26]. In line with this, Su (2017) stated that when learners are actively engaged in learning, they will positively affect learning outcomes [13].…”
Section: Positive Relationship Between Gameplay Flow and Learning mentioning
confidence: 99%
“…Flow is the state of complete absorption and concentration of an activity by the student as it enhances the learning experience [48]. Studies have shown that flow experience has a positive impact on memory and understanding [26], so when learners are actively engaged in learning, they can positively affect learning outcomes [13].…”
Section: The Relationship Between Gameplay Flow and Learning Perfomentioning
confidence: 99%